2015
DOI: 10.1016/j.medici.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean section rates in Lithuania using Robson Ten Group Classification System

Abstract: Women in Groups 1, 2 and 5 were the largest contributions to the overall CS rate in Lithuania. It seems that efforts to reduce the overall CS rate should be directed on increasing vaginal birth after CS and reducing CS rates in nulliparous women with single cephalic full-term pregnancy (Groups 1 and 2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
27
2
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 15 publications
5
27
2
4
Order By: Relevance
“…As showed in our study, when analysing the CS rates, the main contributing groups to overall CS rate were group 5,1 and 2, giving contribution rate of 71,64%, which is similar to other studies (3,12,17,18), although they make just 18,82% of all deliveries as we can see in picture 2.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As showed in our study, when analysing the CS rates, the main contributing groups to overall CS rate were group 5,1 and 2, giving contribution rate of 71,64%, which is similar to other studies (3,12,17,18), although they make just 18,82% of all deliveries as we can see in picture 2.…”
Section: Discussionsupporting
confidence: 91%
“…When compared with other studies internationally, almost all studies convayed comparable results in groups 6-10 (3,12, 17). …”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…16 The cesarean rate in both Brazil and the private sector in Australia has in fact been found to be high or around 47%. [2][3][4][5][6]13,15,17 In countries with lower cesarean rates such as The Netherlands (16%), France (21%), or the Nordic countries (15%-21%), the cesarean rate in group 5 has been found to be around 40%-60%, 7,8,14 which is similar to that observed in our study. In France, the relative size of group 2b was 1.5% and the size of group 4b was 0.7%.…”
Section: Discussionsupporting
confidence: 89%
“…2 The size of group 5 is usually related to the overall cesarean rate, and if this group is large or over 15%, it could mean that the cesarean rate is high in that particular setting. [2][3][4][5][6]13,15,17 The cesarean rate in this group was noticeably lower in our study at 55.5%. 2,4 Our study also indicated that Robson groups 2b and 4b, planned cesarean at term, were relatively small at 0.3% and 0.7%.…”
Section: Discussioncontrasting
confidence: 55%